Evaluation of Validity and Reliability of Persian Version of Questionnaire Entitled: "The Impact of Fixed Orthodontic Appliances on the Daily Life of the Patients" - Sadaf Akbari; Reza Ghorbanipour; Mohammad Mehdi Naghibi; Sedigheh Sheikhzade; Hemmat Gholinia (Mashhad University of Medical Sciences, 2023)
Introduction: The present study aimed to design a questionnaire entitled "The Impact of Fixed Orthodontic Appliances on the Daily Life of the Patients", followed by the assessment of its reliability and validity.Materials and Methods: A questionnaire entitled "The Impact of Fixed Orthodontic Appliances on the Daily Life of the Patients" was developed in eight domains. The questionnaire was distributed among 10 patients with fixed orthodontic appliances and was modified based on their views for the evaluation of face validity. Subsequently, it was redistributed among 30 patients within a 10-day interval to assess test-retest reliability. Finally, the Oral Health Impact Profile-14 (OHIP-14) and the questionnaire developed in the present study were completed by 300 patients whose orthodontic appliances were in place for at least six months. They were treated in the Department of Orthodontics in the School of Dentistry at Babol University of Medical Sciences. The data were analyzed in SPSS software (version 22) through Pearson coefficient and independent sample t-test.Results: The test-retest reliability was assessed using Cronbach's alpha and obtained at 0.817. According to the results of the intra-class correlation coefficient, the responses of 10 people to the questionnaire were consistent before and after a 10-day interval, and the agreement between responses to the two questionnaires was determined at 64%. The respondents were most and least dissatisfied with functional limitation (3.37 of 5) and ​​physical impact (1.59 out of 5), respectively.Conclusion: The questionnaire designed in this study had acceptable validity and reliability. This questionnaire assessed the impact of the fixed orthodontic appliances on eight domains of aesthetics and social impact, functional limitations, nutrition, oral hygiene, maintenance effect, physical impact, time constraints, and travel cost.